The Role of Wonderful Indonesia Website in Supporting Digital Tourism Marketing: Performance Analysis and Its Impact - Asep Koswara (CV Projurnal Mitra Publikasi, 2025)
This study examines the role of the Wonderful Indonesia website (www.indonesia.travel) in supporting digital tourism marketing and its impact on foreign tourist arrivals. Utilizing a descriptive quantitative approach, the research analyzes the website's performance using digital marketing tools, specifically app.neilpatel.com, to evaluate key metrics such as website traffic, SEO performance, and keyword rankings. The study reveals that the website has achieved significant organic traffic, generating 6 million organic visitors and maintaining a strong domain authority score of 69. Popular keywords including